Creating Urban Sociality in Middle‐Class Neighborhoods in Milan and Bologna: A Study on the Social Streets Phenomenon. (1st July 2019) - Morelli, Niccolò
Abstract: Social Streets are groups of neighbors who want to recreate convivial ties having noticed a weakening of social relationships in their roads of residence. Social Streets start as online Facebook groups to materialize in offline encounters, using conviviality to create virtuous bonds. These are carried out through practices of sociality, inclusive and for free. The main focus of this article is analyzing sociodemographic data of the "Streeters" and of the neighborhoods to understand where they produce conviviality in urban neighborhoods. To do this, the article examines two Italian cities which have the highest number of Social Streets: Milan (72) and Bologna (65). Sociodemographic data from the online survey on "Streeters" in Milan (618 respondents) and Bologna (577 respondents), together with census data from 2011 provided by Istat, have been used. Results show that most "Streeters" are not originally from Bologna and Milan, have a high level of education, and are fully embedded in civic engagement. Through conviviality, Social Streets produce a sense of attachment and can represent a good tool to fight isolation and loneliness in the urban setting.